2011
DOI: 10.1002/mop.25893
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultrawideband monopole antenna with miniaturized size

Abstract: there are four transmission zeros and three resonant frequencies (even-mode frequency f m 1 , odd-mode frequency f m 2 , and the resonant frequency created by the parallel-coupling line). The transmission zeros T z 2 and T z 4 near the lower cutoff frequency and in the upper-stopband are attributed to the ended-coupling between the 50 X input/output feed lines. When compared with the simulated result of the filter without the loaded identical short stubs, two additional transmission zeros T z 1 and T z 3 can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…It is noted that the patterns of the current distribution matches the conditions of magnetic mirror symmetry. Some researchers have shown that chopping off half of the symmetrical monopole antenna retains one strong current path and can operate over a wider bandwidth [45][46][47][48][49][50][51]. Degradation in the cross-polarization level is reported as a limitation to this technique [52,53].…”
mentioning
confidence: 99%
“…It is noted that the patterns of the current distribution matches the conditions of magnetic mirror symmetry. Some researchers have shown that chopping off half of the symmetrical monopole antenna retains one strong current path and can operate over a wider bandwidth [45][46][47][48][49][50][51]. Degradation in the cross-polarization level is reported as a limitation to this technique [52,53].…”
mentioning
confidence: 99%